An investigation of low cycle fatigue properties, deformation characteristics and fracture behaviour of the Ti-6Al-1.7Zr-3.3Mo-0.3Si alloy: Influence of temperature, strain rate and hold period - Singh B.K.; Singh P.N.; Singh V. (My University, 2025)
Low Cycle Fatigue (LCF) behaviour of the α+β type high temperature titanium alloy Ti-6Al-1.7Zr-3.3Mo-0.3Si (GTM 900) was studied in the α+β solution treated, air cooled and stabilized condition at different total strain amplitudes, at room temperature and 773K. It was observed from the cyclic stress response curves that there was continuous and extensive softening at room temperature. However, at 773K there was only mild softening during the initial 60 to 200 cycles and it was followed by stabilization of stress in the subsequent cycles and finally by secondary hardening in the terminal stage, in particular at lower strain amplitudes (Δε t/2 < ± 1.1%). The tendency for hardening at 773K increased with lowering of cyclic frequency and introduction of tensile hold period. Further, while there was a single slope in the plot of the total strain amplitude (Δεt/2) verses the number of reversals to failure (2Nf), there was dual slope in the Coffin-Manson plot (Δεp/2 verses 2Nf) both at room temperature as well as 773K. Dual slope in the C-M plot was found to be associated with inhomogeneous deformation by planar slip, at low strain amplitudes. The microstructure of the alloy, following tensile hold during LCF at 773K, was found to be considerably modified.